The Role of the Arab Descendants in Islamic Preaching and the Development of Religious Education in West Sulawesi: Tracing the Significance of the Role and The Their Impacts on the Development in Polewali, Mandar - bodi, idham khalid (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
The coming and development of Islam in a region could not be separated from the role of ulama (Islamic scholars or preachers), i.e. the local ulama and the Arab-descendant ulama. In Mandar (West Sulawesi) some names of ulama worth mentioning included Syekh Abdurrahim Kamaluddin, Syekh Abdul Mannan, Raden Mas Suryo Adilogo, Syekh Zakaria al Maghribi, etc. Of those ulama, some came from several regions in the Indonesian archipelago, some were Arab descendants, and some even came directly from the Middle east. However, those earliest preachers only left traces of history. Today their genealogical descendants are no longer found. There was their genealogical vacuum until the end of 19th century. This research analyzes the role of the Arab descendants in in Polewali Mandar, West Sulawesi, by putting forward two questions, namely: 1) How was the picture of the spread of the Arab descendants in Polewali Mandar, West Sulawesi? And how was the institutional system built by the Arab descendants in Polewali Mandar, West Sulawesi? To investigate, this research used a qualitative descriptive approach. The results of research showed that the first entry and development of the Arab descendants in Mandar were marked by the coming of the Arab-descendant preacher named Syekh Alwi bin Abdullah bin Sahl (circa 1880s). Until today, the Arab descendants spreading in Mandar have come from his clan, followed by other Arab descendants coming from other clans. Keywords: the Arabs, educational institution, the Arab descendants